The Effect of Pelayanan Quality on Public Satisfaction at Barung-Barung Balantai - Mayliza, Riri; Alba, Fegi Jeans (Bina Bangsa International Journal of Business and Management, 2023)
This study aims to examine the effect of physical evidence, reliability, responsiveness, assurance, and empathy on community satisfaction at the wali nagari barung-barung balantai office. This type of research is quantitative, the research process emphasizes the measurement of objective results using statistical analysis. The population in this study is the Barung Barung Balantai community. The total population is 2,853 people. The sampling technique used is purposive sampling which is based on certain criteria, namely the people who perform services at the wali nagari barung-barung balantai office, while the number of samples is 78 people obtained by classifying the community. The data analysis technique used multiple linear regression using the SPSS version 21.00 program. The results of this study indicate that physical evidence, reliability, responsiveness, assurance, and empathy for community satisfaction have a positive and significant effect on community satisfaction at the wali nagari barung-barung balantai office